KINERJA KEUANGAN PERUSAHAAN DITINJAU DARI PERBEDAAN STRUKTUR MODAL - AMELIA HARTINIGRUM, RAHAYU (Jurnal Akuntansi AKUNESA, 2017)
This research aims to determine whether financial performance of companies that have larger number of debt are different with companies that have less debt. This study uses comparative method and non parametric hypotheses Mann-Whitney t-test since the data is not comply  with normality assumption. The sample consists of published companies on Indonesia Stock Exchange (IDX) on 2015, excluding financial sector, that have DER ratio ranging from more than 1 and less than 1. The result indicates that financial performance of companies that have larger numbers of debt differ from those with lower debt. Keyword:capital structure,debt level, firm performance